(untitled) (Research, Society and Development, 2024)
The introduction of Information and Communication Technologies (ICT) in the educational process is a necessary step for improving the quality of education, as it keeps pace with the rapid pace of technological progress. This study aims to explore primary school teachers’ views on the usefulness and challenges they face in integrating ICT into their teaching. For the study, qualitative research was conducted through semi-structured interviews with six primary school teachers working in a 6/seat provincial primary school who use ICT in the educational process. The interviews were analysed using the thematic analysis method. The findings of the thematic analysis revealed four main themes: 1) the usefulness of ICT, 2) the types of ICT used, 3) the difficulties teachers face in using ICT, and 4) strategies for managing these difficulties. In particular, ICT improves the quality of the educational process, enhances student participation and interest, and improves educational outcomes for students with special educational needs, such as learning difficulties. The types of ICT preferred are computers, projectors, the Internet, educational videos and software games. The main difficulties identified include a lack of logistical infrastructure, limited teacher time based on the curriculum and insufficient teacher training. Strategies to manage these difficulties include initiatives to acquire equipment through Christmas bazaars, teacher adaptability and the need to attend training programmes. Suggestions for future research include expanding the sample and exploring the views of students and parents.